Did Inflation and the Exchange Rate Increase Indonesia's Budget Deficit? - Hastuti, Diah Retno Dwi; Asriyani,; Abd. Rahim, (Bulletin of Economic Studies (BEST), 2023)
This study aims to determine the effect of inflation and exchange rates on the budget deficit in Indonesia. The type of data used in this research is secondary data and is a time series data for 2000-2020. The method of analysis in this study is a linear regression with the Ordinary Least Square (OLS) technique. Based on the analysis results, partial inflation significantly negatively affects Indonesia's budget deficit. In contrast, the exchange rate significantly positively affects Indonesia's budget deficit. Simultaneously inflation and exchange rates significantly affect Indonesia's budget deficit.